IMPROVING TEACHER ABILITY IN DEVELOPING HOTS BASED RPP THROUGH WORKSHOP AT UPT SD NEGERI SUTOJAYAN 03 - Endang Sujarwati; Isna Nurul Inayati (Universitas Islam Raden Rahmat Malang, 2022)
The results of observations at SD Negeri Sutojayan 03 show that some teachers still do not have good skills in preparing HOTS-based learning implementation plans. To address this, the researchers plan to carry out school action research with the theme ofincreasing teachers' abilities in preparing HOTS-based lesson plans. This type of research is school action research. This research was conducted at SD Negeri Sutojayan 03 in November 2021 with the research subjects being all teachers at SD Negeri Resapombo. The technique of collecting data from this school action research is through qualitative data obtained from observation/observations, interviews and document studies. This procedure includes the following stages: (1) planning, (2)implementation, (3) observation, and (4) reflection. Based on the results of reflection, monitoring and evaluation that have been carried out, it can be concluded that cycle 1 and cycle 2 activities have increased so that all objectives of this school action research activity are declared successful.